2001
DOI: 10.1021/ja003944x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Mechanism of Alkane Reductive Elimination and Skeletal Isomerization in Tp‘Rh(CNneopentyl)(R)H Complexes:  The Role of Alkane Complexes

Abstract: Experiments are described that provide indirect evidence for the involvement of alkane sigma-complexes in oxidative addition/reductive elimination reactions of Tp'Rh(L)(R)H complexes (Tp' = tris-3,5-dimethylpyrazolylborate, L = CNCH(2)CMe(3)). Reductive elimination rates in benzene-d(6) were determined for loss of alkane from Tp'Rh(L)(R)H, where R = methyl, ethyl, propyl, butyl, pentyl, and hexyl, to generate RH and Tp'Rh(L)(C(6)D(5))D. The isopropyl hydride complex Tp'Rh(L)(CHMe(2))H was found to rearrange to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
108
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(126 citation statements)
references
References 50 publications
17
108
0
1
Order By: Relevance
“…After clean activation of acetonitrile, it was observed that 2 was stable indefinitely at room temperature in the presence of benzene. Previously, it had been reported that upon formation of alkyl hydride complexes via COH bond activation of alkanes, the complexes would undergo reductive elimination in the presence of benzene to form 6 and free alkane with half lives of Ϸ5 h (methane) to Ϸ1 h (ethane-hexane) (46). The studies investigated here show that the nitrile-containing complexes are much more stable with the stability of the complex being dependent on the chain length of the alkylnitrile.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…After clean activation of acetonitrile, it was observed that 2 was stable indefinitely at room temperature in the presence of benzene. Previously, it had been reported that upon formation of alkyl hydride complexes via COH bond activation of alkanes, the complexes would undergo reductive elimination in the presence of benzene to form 6 and free alkane with half lives of Ϸ5 h (methane) to Ϸ1 h (ethane-hexane) (46). The studies investigated here show that the nitrile-containing complexes are much more stable with the stability of the complex being dependent on the chain length of the alkylnitrile.…”
Section: Discussionmentioning
confidence: 64%
“…The electron-withdrawing cyano group appears to strengthen the RhOC bond, raising the energy required to reach the transition state for COH reductive elimination. Although the detailed mechanism by which these eliminations occur has not been investigated, they are likely to proceed via initial reductive coupling to make -COH complexes, which then dissociate from the metal, as in the alkane analogs (46).…”
Section: Discussionmentioning
confidence: 99%
“…Observation of the rearranged product indicates a unimolecular pathway that is consistent with -alkane complexes as intermediates (22). By studying the kinetics of rearrangements of a series of alkyl deuteride complexes, and by kinetic modeling of the rearrangements, including a determination of isotope effects (27), the relative barrier heights for C-H oxidative cleavage, migration from one C-H bond to an adjacent C-H bond, and dissociation of the alkane from the metal were determined (22). Although this study did not provide an indication of the energies of either the methyl or methylene -alkane complexes, it did provide energy differences between the various processes available to the -alkane complexes.…”
mentioning
confidence: 72%
“…The thermodynamic preference for the former substrate was found to be 2.07 kcal⅐mol Ϫ1 (1 kcal⅐mol Ϫ1 ϭ 4.18 kJ⅐mol Ϫ1 ), which, when corrected for statistical factors, corresponds to a 95:1 preference for activation of methyl over methylene C-H bonds. § Confirmation of this conclusion comes from the independent synthesis of the isopropyl complex TpЈRh(CNR)(CHMe 2 )H, which rearranges in benzene solution to the more stable n-propyl isomer TpЈRh(CNR)(CH 2 CH 2 CH 3 )H before loss of propane (22).…”
mentioning
confidence: 89%
See 1 more Smart Citation